The Popular and the Sacred in Music - Kärjä, Antti-Ville (Taylor & Francis, 2022)
Music, as the form of art whose name derives from ancient myths, is often thought of as pure symbolic expression and associated with transcendence. Music is also a universal phenomenon and thus a profound marker of humanity. These features make music a sphere of activity where sacred and popular qualities intersect and amalgamate. In an era characterised by postsecular and postcolonial processes of religious change, re-enchantment and alternative spiritualities, the intersections of the popular and the sacred in music have become increasingly multifarious. In the book, the cultural dynamics at stake are approached by stressing the extended and multiple dimensions of the sacred and the popular, hence challenging conventional, taken-for-granted and rigid conceptualisations of both popular music and sacred music. At issue are the cultural politics of labelling music as either popular or sacred, and the disciplinary and theoretical implications of such labelling. Instead of focussing on specific genres of popular music or types of religious music, consideration centres on interrogating musical situations where a distinction between the popular and the sacred is misleading, futile and even impossible. The topic is discussed in relation to a diversity of belief systems and different repertoires of music, including classical, folk and jazz, by considering such themes as origin myths, autonomy, ingenuity and stardom, authenticity, moral ambiguity, subcultural sensibilities and political ideologies.